Inter-operator variability in the sensitivity of sentinel lymph node biopsy for melanoma - Harrison, C; Rodrigues, J; Cassell, O (Elsevier, 2018)
Introduction and aims: Plastic surgery trainees, in some circumstances, can progress to consultant level having performed only 15 generic lymph node surgeries, with no mention specifically of sentinel lymph node biopsy (SLNB) on the training log. The majority of SLNBs carried out for melanoma at our centre since 1999 have been performed by eight surgeons, six of whom had been formally trained and mentored in our unit or previously completed skin cancer fellowships. Two surgeons started performing the procedure without formal training or specialist fellowships. We analysed the first 40 cases performed by each consultant hypothesising that those with more extensive training would achieve higher sensitivities. Methods: Using our centre's prospectively collected data set we studied 320 procedures. Sensitivities were calculated and compared between surgeons with less extensive and more extensive training. Results: The two surgeons without formal training had a combined sensitivity of 85% (80 cases, 17 positive results, 3 false negative results). The six surgeons who had been practising after extensive training had a combined sensitivity of 94% (240 cases, 44 positive results, 3 false negative results). SLNBs in the head and neck region accounted for 17% of total cases, but 50% of false positive results. Conclusions: There is likely to be a learning curve for this operation, and in the era of adjuvant therapy a false negative result may affect survival. Training requirements may not be enough to ensure consistency amongst newly qualified plastic surgeons. We advocate a similar level of experience to that required of breast surgeons before performing the procedure independently.